2017
DOI: 10.1007/s40091-017-0173-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal shape control of piezolaminated beams with different boundary condition and loading using genetic algorithm

Abstract: Piezoelectric actuators are effectively used to control the response of light weight structures in shape, vibration and buckling. Optimization for the shape control of piezoelectric beam is the recent challenge which requires proper numerical technique to perform. The shape control of a composite beam using surface-bounded piezoelectric actuators has been investigated in the present work. The mathematical model is developed using twonode Timoshenko beam element coupling with the theory of linear piezoelectrici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Considering a beam with surface bounded piezoelectric patches. The coupling relationship between the electrical and mechanical behavior of the smart piezoelectric beam [4,22] can be described as:…”
Section: Theoreticalmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering a beam with surface bounded piezoelectric patches. The coupling relationship between the electrical and mechanical behavior of the smart piezoelectric beam [4,22] can be described as:…”
Section: Theoreticalmentioning
confidence: 99%
“…Based on the Timoshenko's beam theory, and using Hamilton's principle with two node beam element the governing mechanical equation of motion of the smart beam can be written as (see [22]):…”
Section: Theoreticalmentioning
confidence: 99%
“…The indices p, a and s represent the plate, the actuator and the sensor elements, respectively. According to [24], the global matrix equations governing the present SSP can be written as:…”
Section: Dynamic System Equationmentioning
confidence: 99%
“…Results have shown that the electromechanical coupling can strengthen the plate's resistance to vibration. Bendine and Wankhade (2017) used piezoceramic elements to control the shape control of beams with different boundary condition and loading.…”
Section: Introductionmentioning
confidence: 99%